Selective inhibition of topoisomerases from Pneumocystis carinii compared with that of topoisomerases from mammalian cells. - Dykstra, C C (1994)
Type I and II topoisomerase activities were partially purified from Pneumocystis carinii. The catalytic (strand-passing) activities of both enzymes were selectively inhibited by members of a series of dicationic-substituted bis-benzimidazoles compared with those of topoisomerases of mammalian (calf thymus) origin. The most active inhibitors of the parasite enzymes were also highly effective in an in vivo animal model of P. carinii pneumonia. Selected dicationic-substituted bis-benzimidazoles also strongly inhibited the induction of the topoisomerase I- and II-mediated cleavable complex, suggesting that the biologically active DNA minor groove-binding molecules inhibit the enzyme-DNA binding step of the topoisomerase reaction sequence. The apparent selectivities for the parasite enzymes and the low levels of toxicity to mammalian cells for the biologically active bis-benzimidazoles suggest that these compounds hold promise as effective therapeutic agents in the treatment of a life-threatening AIDS-related disease, P. carinii pneumonia.